PENGEMBANGAN FLIPBOOK BIOLOGI PADA MATERI SISTEM EKSKRESI UNTUK PEMBELAJARAN YANG MENARIK PESERTA DIDIK KELAS XI DI MAS MUHAMMADIYAH NANGAHURE - Hartini, Nur; Fitriah, Fitriah; Syafriati, Yulimira (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
The creation of a flipbook instructional tool for the kelas XI ekskresi system topic is initiated due to minimal reading enthusiasm among students and the predominant use of traditional teaching aids like printed book formats and worksheets by instructors at mas muhammadiyah nangahure, thus inspiring a flipbook-based innovation to cultivate an enjoyable and non-repetitive learning atmosphere. This research endeavors to produce flipbook-based learning media for the ekskresi system subject at mas muhammadiyah nangahure. The study utilizes a Research and Development (R&D) approach, following the Borg and Gall model's five procedures: a preliminary investigation, research planning, design formulation, a constrained field uji, and revisions from the limited trial's feedback. The validation assessments of the flipbook learning media product for the ekskresi system material were rated "very suitable" by the content expert validator with a score of 80% and by the media expert validator with a score of 81%. The outcomes from the flipbook product's trial feedback concerning the ekskresi System Material developed are declared "high" by students with the percentage of student response by 95,24%.Kata kunci: Learning Media, Flipbook, and Excretion System.